2013
DOI: 10.1099/mic.0.071084-0
|View full text |Cite
|
Sign up to set email alerts
|

Two potentially novel amylolytic enzyme specificities in the prokaryotic glycoside hydrolase α-amylase family GH57

Abstract: Glycoside hydrolase (GH) family 57 consists of more than 900 proteins from Archaea (roughly one-quarter) and Bacteria (roughly three-quarters), mostly from thermophiles. Fewer than 20 GH57 members have already been biochemically characterized as real, (almost exclusively) amylolytic enzymes. In addition to a recently described dual-specificity amylopullulanasecyclomaltodextrinase, five enzyme specificities have been well established in the familya-amylase, amylopullulanase, branching enzyme, 4-a-glucanotransfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…1 a). The tree contains clusters of family GH57 enzymes, such as α-amylase, 4-α-glucanotransferase, amylopullulanase, bifunctional amylopullulanase–cyclomaltodextrinase, maltogenic amylase, α-galactosidase, non-specified amylase and α-glucan branching enzyme, well established by previous studies (Blesak and Janecek 2012 , 2013 ). With regard to their mutual evolutionary relationships, α-amylase are clustered together with 4-α-glucanotransferase; both being in a closer relatedness with amylopullulanases and their bifunctional counterparts possessing also the cyclomaltodextrinase specificity.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…1 a). The tree contains clusters of family GH57 enzymes, such as α-amylase, 4-α-glucanotransferase, amylopullulanase, bifunctional amylopullulanase–cyclomaltodextrinase, maltogenic amylase, α-galactosidase, non-specified amylase and α-glucan branching enzyme, well established by previous studies (Blesak and Janecek 2012 , 2013 ). With regard to their mutual evolutionary relationships, α-amylase are clustered together with 4-α-glucanotransferase; both being in a closer relatedness with amylopullulanases and their bifunctional counterparts possessing also the cyclomaltodextrinase specificity.…”
Section: Resultssupporting
confidence: 57%
“…Of these, 1568 sequences were retrieved from the family GH57 of the CAZy database directly, whereas remaining 34 sequences of the specificity of maltogenic amylase were obtained using the BLAST. This was because the three biochemically characterized maltogenic amylases have still not been classified within the family GH57, although previous in silico analysis (Blesak and Janecek 2013 ) along with cloning, sequencing and structural studies (Comfort et al 2008 ; Jeon et al 2014 ; Jung et al 2014 ; Park et al 2014 ) have clearly suggested they exhibit all sequence/structural features characteristic of the family GH57.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and others (), Ballschmiter and others (), and Zhang and Zeng () reported on amylases from many different extreme environments. In an effort to understand the mechanism of action of GH 57 amylase family, in relation to structure, Blesak and Janecek () studied 2 partially characterized GH 57 nonspecified amylases from an uncultured bacterium by bioinformatics analysis. Though the study found the enzyme hydrolyzing soluble starch, specificities and the reaction products could not be determined.…”
Section: α‐Amylase Familymentioning
confidence: 99%
“…Twenty years ago, several α-amylases and related enzymes composed of a (β/α) 7 -barrel (an irregular TIM-barrel domain) were classified into the family GH57; more recently also the family GH119 was established910. Both of these enzyme families are at present considerably smaller than GH13 and only few members have been characterized in detail11.…”
mentioning
confidence: 99%